Grenzfragen von den Pariser Vorortverträgen bis zum Ersten Wiener Schiedsspruch 1938 und seine Folgen - Hamza, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The first part of the article is dealing with the political negotiations, in particular, the one after the Munich Agreement, defining a three-month period to resolve Hungarian demands, to the First Vienna Award signed on November 2, 1938 at the Belvedere Palace in Vienna. The First Vienna Award separated predominantly Hungarian-populated territories in southern Slovakia and southern Carpathian Rus from Czechoslovakia and awarded them to the Kingdom of Hungary. Hungary thus regained some of the territories in present-day Slovakia and Ukraine lost in the Peace Treaty of Trianon. In the second part of the study the author is analyzing the negotiations following the First Vienna Award. The recovered territories were incorporated into Hungary (Kingdom of Hungary) on November 12, 1938, by a legislative act of the Hungarian Parliament.